Development of an IoT Tool for Optimizing Humidity Control in Cocoa Cultivation - Santillán, Hólger; Suárez, Michael; Cárdenas, David (Memoria, investigaciones en ingeniería, 2023)
The following document presents the development of a humidity sensor for cocoa crops using IoT and Arduino. Its purpose is to showcase the various applications that new technologies can offer, particularly in the cocoa industry. It involves designing a humidity sensor node to measure changes in humidity and temperature using the electronic design tool Proteus. The measurement module is programmed in Arduino IDE and connected to the cloud via IoT, incorporating Node-RED as a means to remotely visualize real-time results. This is achieved through a presentation dashboard as the final output of the measurement process, collecting data on climate changes received by the transducer and comparing them with data obtained from the web over a specified period. This process verifies the sensor's efficiency and data accuracy, setting a precedent for future research in applied electronics, IoT, and telecommunications.